2011
DOI: 10.4236/ojml.2011.12004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Word Order Alternation on the Sentence Processing of Sinhalese Written and Spoken Forms

Abstract: In both written and spoken forms, the Sinhalese language allows all six possible word orders for active sentences with transitive verbs (i.e., SOV, OSV, SVO, OVS, VSO, and VOS), even though its unmarked order is subject-object-verb (SOV) (e.g., Gair, 1998; Miyagishi, 2003; Yamamoto, 2003). Reaction times for sentence correctness decisions showed SOV < SVO = OVS = OSV = VSO = VOS for the written form, and SOV < SVO = OVS < OSV = VSO = VOS for the spoken form. The different degrees of reaction times may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 8 publications
2
26
0
Order By: Relevance
“…The results of Experiments 1 and 2 provided evidence for scrambling effects in written Sinhalese. Thus, as previous studies (Dissanayaka, 2007;Herath, Hyodo, Kawada, Ikeda, & Herath, 1994;Pallatthara & Weihene, 1966;Tamaoka et al, 2011) indicated, both experiments in the present study also showed that the canonical word order in the Sinhalese language is SOV.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of Experiments 1 and 2 provided evidence for scrambling effects in written Sinhalese. Thus, as previous studies (Dissanayaka, 2007;Herath, Hyodo, Kawada, Ikeda, & Herath, 1994;Pallatthara & Weihene, 1966;Tamaoka et al, 2011) indicated, both experiments in the present study also showed that the canonical word order in the Sinhalese language is SOV.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, previous studies on the Sinhalese language (e.g., Dissanayaka, 2007;Gair, 1998;Miyagishi, 2003) suggest that the flexibility of Sinhalese word order allows sentences to have another five different word orders as OSV, OVS, SVO, VSO, and VOS which also represent the same meaning of that SOV ordered sentence. Tamaoka, Kanduboda, & Sakai (2011) conducted experiments using all these orders. They found that, among them, SOV is the fastest to be processed by native Sinhalese speakers, and concluded that SOV is the canonical order from the psycholinguistic perspective.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with an incremental processing system that bears predictive mechanisms: the processor makes predictions on the upcoming words based on the input information received by far. Since Japanese has an explicit case-marking system, it is likely that the processor takes advantages of the case markers during real-time comprehension (Kahraman et al, 2010;Kamide et al, 2003;Miyamoto, 2002Miyamoto, , 2003Tamaoka et al, 2005Tamaoka et al, , 2011Sato et al, 2009;Yamashita, 1997Yamashita, , 2000. Specifically, in our transitive sentences, the critical verbs were preceded by an object NP that carried an accusative case marker -o (ACC).…”
Section: Discussionmentioning
confidence: 99%
“…Japanese employs SOV and OSV; all the six logically possible orders are actually used in Finnish; and so on. It has been observed, in many flexible as well as rigid word order languages, that the syntactically basic word order is easier to process than the other grammatically possible word orders (derived word orders) (Bader & Meng, 1999 for German, Kaiser & Trueswell, 2004 for Finnish, Kim, 2012 for Korean, Mazuka, Itoh, &Kondo, 2002 andTamaoka et al, 2005 for Japanese, Sekerina, 1997 for Russian, Tamaoka, Kanduboda, & Sakai, 2011 for Sinhalese). 1 In Japanese, for example, sentences with the syntactically basic SOV order are processed faster than comparable OSV sentences according to various psycholinguistic studies using sentence plausibility judgment tasks (Chujo, 1983;Tamaoka et al, 2005), self-paced reading (Koizumi & Imamura, 2017;Shibata et al, 2006), and eye tracking (Mazuka et al, 2002;Tamaoka et al, 2005).…”
Section: Introductionmentioning
confidence: 99%